MENILAI KINERJA PERUSAHAAN DENGAN MENGGUNAKAN ANALISIS RASIO KEUANGANPADA PT KABELINDO MURNI TBK - Azmi, Ika Nur; Sastrawan, Rahman (Department of Accounting, Faculty of Economics & Business, 2024)
This research aims to analyze the financial performance of PT. Kabelindo Murni, Tbk in 2018-2022 uses financial ratios in the form of liquidity ratios, solvency ratios, activity ratios, profitability ratios and profit growth ratios. This research uses a quantitative descriptive method with secondary data in the form of company financial reports and then analyzed. The research results show that the company's performance in 2018-2022 can be seen from the liquidity ratio through the current ratio which is quite good, while through the cash ratio and quick ratio it is quite good. The company's performance in 2018-2022 seen by the solvency ratio, activity ratio, and growth ratio using sales growth can be said to be very good, while seen using the profitability ratio and profit growth ratio, including the net profit growth ratio, it can be said that the company's performance in 2018-2022 is poor. Good.